Designing Carbon Nanotube-Based Oil Absorbing Membranes from Gamma Irradiated and Electrospun Polystyrene Nanocomposites - Hemalatha Parangusan (6556133) (2019)
Carbon-based materials are outstanding candidates for oil spill clean-ups due to their superhydrophobicity, high surface area, chemical inertness, low density, recyclability, and selectivity. The current work deals with the fabrication of membrane oil absorbents based on carbon nanotube (CNT) reinforced polystyrene (PS) nanocomposites by electrospinning technique. The spun membranes are also irradiated with the gamma radiation to induce enough crosslinks and thus good polymer-filler interactions. The structural, morphological, and surface properties in addition to the oil/water separation efficiency were investigated by varying the concentration of CNT and the dose of γ-irradiation. Fabricated nanofiber membranes show superior hydrophobicity and selective oil absorption at 0.5 wt.% of CNT concentration. The best mechanical properties are also obtained at this particular concentration and at 15 KGy optimum γ-irradiation dosage. The gamma irradiated PS/0.5 wt.% CNT membrane also exhibits good antibacterial effects against the bacteria, Escherichia coli, in the form of bacterial inhibition rings around the membranes. The present study thus shows the environmental applicability of the fabricated PS/CNT membranes in treating oil-contaminated water. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma12050709